The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/14719037.2018.1473477
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of barriers to public sector innovation process

Abstract: This article provides a systematic review of the empirical literature on barriers within public sector innovation processes, based on data from 63 articles. We investigate the nature of barriers. The studies were analysed based on four dimensions of barriers: i) their classification; ii) their interrelations; iii) whether they play distinct roles within stages of innovation process and iv) whether they vary in the types of innovations. We develop an empirically based framework to capture the complex nature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
230
2
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(254 citation statements)
references
References 89 publications
11
230
2
11
Order By: Relevance
“…Our findings make a broader contribution to studies of public procurement by showing how policies focused on social justice can become diluted when there are shifts in the desired outcomes that government is trying to 'buy' (McCrudden 2007). Our findings align with recent studies that have identified how a lack of clarity about policy goals (Martin, Berner, and Bluestein 2007) and contradictory policy expectations can complicate the public procurement process (Cinar, Trott, and Simms 2019;Knutsson and Thomasson 2014;van Buuren, Eshuis, and Bressers 2015). Prior research has highlighted the potential conflicting goals of public procurement policy related to the competing regulatory, commercial and socio-economic objectives (Erridge 2007).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our findings make a broader contribution to studies of public procurement by showing how policies focused on social justice can become diluted when there are shifts in the desired outcomes that government is trying to 'buy' (McCrudden 2007). Our findings align with recent studies that have identified how a lack of clarity about policy goals (Martin, Berner, and Bluestein 2007) and contradictory policy expectations can complicate the public procurement process (Cinar, Trott, and Simms 2019;Knutsson and Thomasson 2014;van Buuren, Eshuis, and Bressers 2015). Prior research has highlighted the potential conflicting goals of public procurement policy related to the competing regulatory, commercial and socio-economic objectives (Erridge 2007).…”
Section: Discussionsupporting
confidence: 85%
“…Our use of critical discourse analysis has allowed us to illustrate how competing discourses shifted the focus of Indigenous public procurement policy from a progressive affirmative action agenda to a regressive, neo-liberal self-help agenda. The coupling of Indigenous procurement with the broader 'closing the gap' agenda shows how political meaning and contemporary political context can shape the policy transfer process (Korteland and Bekkers 2008;Lovell 2016) and influence the development and implementation of public procurement policy (Cinar, Trott, and Simms 2019). Our analysis highlights how increasingly conservative governments aligned the Indigenous procurement policy with the broader shift towards 'neoliberal sensibilities that seek to individualize a wide range of social ills' (Murray 2004, 50) and a neo-liberal agenda in relation to 'closing the gap' for Indigenous Australians (Pholi, Black, and Richards 2009;Howard-Wagner 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, such analysis can also inform system level policy making in ways that more purposefully foster organization level designs that are conducive to intended outcomes. This recommendation is especially promising for entrepreneurial initiatives in the public sector, such as the ACSS, where progress is often stifled by system-level governance models that are poorly structured and inadequately equipped to foster and support innovation (Cinar et al 2019;Levine and Wilson 2013;Mergel 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Brandsen et al (2016, p. 307), for example, highlight that innovations are often precarious and vulnerable. The same authors also stress that, interesting ideas are often implemented at a small scale but do not result in broader changes (for a recent overview: Cinar et al, 2019). Our article on the dark side of innovation, however, does not focus on barriers in innovation processes and failures to realize a greater impact but on perverse outcomes.…”
Section: Exploratory Overview Of Perverse Effects Of Public Innovationmentioning
confidence: 96%